2006
DOI: 10.1523/jneurosci.2091-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Properties of Cone Signals in Alert Macaque Primary Visual Cortex

Abstract: 7°) than spatial-opponent cell centers (ϳ1°). We found that red-green cells received S-cone input, which aligned with M input, and, unlike blue-yellow cells, red-green cells gave push-pull responses: receptivefield centers of red-ON cells were excited by both L increments (bright red) and M decrements (dark red) and were suppressed by both L decrements (dark green) and M increments (bright green). Excitatory responses to decrements were slightly larger than to increments, which may account for the lower detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
185
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(207 citation statements)
references
References 95 publications
(159 reference statements)
15
185
0
1
Order By: Relevance
“…Some specialized cells in the retina, lateral geniculate nucleus, and V1 show coneopponent responses of the sort that would be expected to be necessary to bring about color perception. But these cells are restricted to encoding only a limited range of colors that does not reflect the dimensions of perceptual color space (21)(22)(23)(24). Colorselective neurons also are found in subcompartments of V2 known as the thin stripes (25), which receive color signals from V1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some specialized cells in the retina, lateral geniculate nucleus, and V1 show coneopponent responses of the sort that would be expected to be necessary to bring about color perception. But these cells are restricted to encoding only a limited range of colors that does not reflect the dimensions of perceptual color space (21)(22)(23)(24). Colorselective neurons also are found in subcompartments of V2 known as the thin stripes (25), which receive color signals from V1.…”
Section: Discussionmentioning
confidence: 99%
“…Our current interpretation of these outliers is as follows. Color-tuned neurons in the extrastriate cortex can have spatially structured chromatically opponent receptive fields (33); moreover, glob cells often are selective for stimulus shape (7), and receptivefield surrounds of color cells tend to have longer latencies than receptive-field centers, at least in V1 where this property has been studied systematically (22). Taken together, these findings suggest that the measured responses of the outliers can be attributed to surround activation, which in turn suggests that the spatial dimensions of the stimulus were poorly matched to the receptive fields of these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromatic preferences of neurons there are broadly distributed throughout the isoluminant plane (Lennie et al, 1990;Wachtler et al, 2003;Johnson et al, 2004;Solomon and Lennie, 2005;Conway and Livingstone, 2006;Horwitz et al, 2007), reminiscent of the higher order color mechanisms inferred psychophysically (Krauskopf et al, 1986;Webster and Mollon, 1994). This suggests that the fundamental mechanisms characterized psychophysically might be established early in V1, at or near the interface with LGN inputs, and that their signals are combined with variable weights before being expressed in the broadly distributed chromatic signatures of most V1 neurons.…”
Section: Introductionmentioning
confidence: 87%
“…This L-M opponent signature is consistent with the results of Chatterjee and Callaway (2003) who reported that SϪ cells (unlike Sϩ cells) responded poorly to LϩM modulation. Among neurons in primary visual cortex that receive substantial input from S-cones, the S-cone input is often aligned with that from M-cones (Conway, 2001;Solomon and Lennie, 2005;Conway and Livingstone, 2006;Horwitz et al, 2007), possibly reflecting input from subcortical SϪ neurons.…”
Section: Differences Between S؉ and S؊ Cellsmentioning
confidence: 99%